2014
DOI: 10.1177/000313481408001028
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index is Predictive of Higher In-hospital Mortality in Patients Undergoing Laparoscopic Gastric Bypass but Not Laparoscopic Sleeve Gastrectomy or Gastric Banding

Abstract: High body mass index (BMI) has been shown to be a factor predictive of increased morbidity and mortality in several single-institution studies. Using the University HealthSystem Consortium clinical database, we examined the impact of BMI on in-hospital mortality for patients who underwent laparoscopic gastric bypass, sleeve gastrectomy, and gastric banding between October 2011 and February 2014. Outcomes were examined within each procedure according to BMI groups of 35 to 49.9, 50.0 to 59.9, and 60.0 kg/m2 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
(22 reference statements)
1
4
1
Order By: Relevance
“…Patients that underwent LSG had a mean loss of 46.66% EBW, with a mean BMI of 64 kg/m2 before surgery and 46.44 kg/m2 after surgery. These results are acceptable and did not have higher complications, coinciding with Villamere that LSG is safe without increased risk 33 . Gonzalez-Heredia's study reported poor weight loss after LSG 34 , however, in our study, the weight loss for patients who underwent LSG was acceptable, even in the long-term follow-up, as demonstrated by Arapis 35 .…”
Section: Discussionsupporting
confidence: 65%
“…Patients that underwent LSG had a mean loss of 46.66% EBW, with a mean BMI of 64 kg/m2 before surgery and 46.44 kg/m2 after surgery. These results are acceptable and did not have higher complications, coinciding with Villamere that LSG is safe without increased risk 33 . Gonzalez-Heredia's study reported poor weight loss after LSG 34 , however, in our study, the weight loss for patients who underwent LSG was acceptable, even in the long-term follow-up, as demonstrated by Arapis 35 .…”
Section: Discussionsupporting
confidence: 65%
“…It is remarkable that the present study showed that a gastric bypass is associated with a higher likelihood (OR) of achieving TO compared to sleeve gastrectomy, while recent literature claims the opposite. [31,32] This is most probably due to the large number of RYGB procedures in the Netherlands and the associated experience gained with this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In all of these patients, the reflux symptoms disappeared in the post-operative period. SG can be performed more easily and safely than other surgical procedures given the large liver volume, limited intraabdominal operating space, increased abdominal wall thickness, and increased abdominal fat tissue [38].…”
Section: Discussionmentioning
confidence: 99%